(untitled) (The International Journal for Scientific Research, 2023)
The researcher noticed, through his exposure to a lot of research and specialized medical studies, and through his visits to physiotherapy centers, that there is no accurate diagnosis of cases of knee deformity(Valgus Knee) and the main reasons that enable the therapist to give appropriate treatment are not identified, and most of the therapeutic exercises are The treatment is given randomly, in which individual differences between the patients are not taken into account, and it does not depend on standardized training loads to achieve the principle of safety, effectiveness, and the desired results of treatment. Therefore, the researcher decided to develop a comprehensive, sequential therapeutic training program, starting with accurate diagnostic steps and ending with two therapeutic training programs, in which the training loads of the sample (intensity, size, and density) are taken into account with external resistance (rubber bands), which is commensurate with the ability of the sample and contributes to the treatment of injury. In order to reach the results of the research, the following objectives were set: 1. Preparing a list of primary diagnostic tests for the experimental research sample. 2. Preparing a list of tests for examining the integrity of the knee joint. 3. Preparing a list of special tests to measure the level of deformity in the knee joint. 4. Preparing a list of special tests to measure strength Leg muscles. 5. Preparing a training program using static muscle stretching method. 6. Preparing a therapeutic training program using (rubber bands). 7. Identifying the effect of the therapeutic training curriculum. The following conclusions were reached: 1. The therapeutic training curriculum using (rubber bands) has a positive effect in raising the level of strength of the muscles of the legs. 2. The curative training curriculum using (rubber bands) has a positive effect in measuring the degree of knee deformity. The researcher recommends the following: · Follow all the steps of the initial examination, to find out the main causes that led to the occurrence of this deformity in the knee joint and choose the appropriate treatment. · The training loads used in the therapeutic training curriculum are commensurate with the ability of the selected sample, and it may not be suitable for all patients with the same type of deformity. Therefore, pre-tests must be conducted for each injured sample to measure the special physical capabilities before developing a therapeutic training program plan.